2022
DOI: 10.35794/emba.v10i3.43526
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh Kualitas Produk Dan Brand Ambassador Kpop NCT Dream Terhadap keputusan Pembelian Pada Produk Mie Lemonilo Di Manado

Abstract: Strategi marketing yang efektif tentunya akan mempengaruhi konsumen dalam membuat keputusan pembelian. Penelitian ini bertujuan untuk melihat Pengaruh Kualitas Produk dan Brand Ambassador Kpop NCT Dream terhadap Keputusan Pembelian pada Produk Mie Lemonilo di Manado. Metode pengambilan sampel menggunakan teknik Purposive Sampling. Sampel yang digunakan adalah sebanyak 100 responden populasi masyarakat kota Manado. Metode analisis yang digunakan adalah analisis regresi linear berganda. Hasil penelitian uji seca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 0 publications
1
2
0
1
Order By: Relevance
“…So H4 was accepted (see Table 8). The results are similar to the study of (Armanda et al, 2017; Makatumpias et al, 2018; Phan et al, 2021) which showed CSR improves brand image significantly. Hypothesis H5 evaluates whether Green Brand Image positively impacts Green Purchase Intention.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…So H4 was accepted (see Table 8). The results are similar to the study of (Armanda et al, 2017; Makatumpias et al, 2018; Phan et al, 2021) which showed CSR improves brand image significantly. Hypothesis H5 evaluates whether Green Brand Image positively impacts Green Purchase Intention.…”
Section: Discussionsupporting
confidence: 90%
“…This method integrates CSR into business differentiation strategy as an equally crucial investment alongside R&D and advertising (Gardberg & Fombrun, 2006). CSR improves brand image significantly (Armanda et al, 2017; Makatumpias et al, 2018; Phan et al, 2021) resulting a positive impact on purchase intentions. In this era, public awareness about the social responsibility of businesses to environmental protection issues is growing sustainability, and resultantly businesses are paying more attention to build their corporate image as socially responsible business to improve their brand image (Dwipamurti et al, 2018).…”
Section: Theoretical Background and Hypotheses Developmentmentioning
confidence: 99%
“…Meanwhile, Yulianti's research (2020) states that green marketing has an insignificant positive effect on consumer satisfaction. Research conducted by Pesoth (2018) shows that packaging has a strong influence on consumer satisfaction. Likewise, research conducted by Trinanda (2021) states that packaging has a significant effect on consumer satisfaction.…”
Section: Introductionmentioning
confidence: 99%
“…Musik pop adalah salah satu dari banyak produk Korean Wave yang sangat diminati oleh generasi milenial (Yusuf et al, 2022). K-pop, atau musik pop Korea, adalah bagian dari industri hiburan yang berkontribusi pada pertumbuhan ekonomi Korea Selatan.…”
unclassified